Pengaruh Model Pembelajaran Kooperatif Tipe Think Pair Share Terhadap Kemampuan Pemahaman Konsep Matematis Siswa Materi Bentuk Aljabar Kelas VII UPTD SMP Negeri 3 Pematang Siantar - Heny Cristina Nainggolan; Belsasar Sihombing; Firman Pangaribuan (CV Putra Publisher, 2023)
The aim of this research aims to see the influence of the Think Pair Share Type Cooperative Learning Model on Students' Ability to Understand Mathematical Concepts in Algebra Form Class VII UPTD SMP Negeri 3 Pematang Siantar. The type of research used in this research is quantitative research, because the data and research are in the form of numbers and require statistical calculations. In this research, the design used is a Pre-Experimental Design in the form of a One Shot Case Study. In this design, there is treatment given to the experimental class, namely the application of the Think Pair Share type cooperative learning model. This research was carried out in class VII UPTD of SMP Negeri 3 Pematang Siantar which is located on Jl. Laguboti Ujung, Martimbang Village, District. South Siantar, Pematang Siantar City. In this research, the sampling technique used is probability sampling with simple random sampling type. Based on the results of the research and discussion previously presented, it can be concluded that there is a positive and significant influence of the Think Pair Share type cooperative learning model on the ability to understand mathematical concepts of class VII students at UPTD SMP Negeri 3 Pematang Siantar Q.A 2023/2024. This influence can be seen through the regression equation Y = 11.572 + 0.140 H1 is accepted and the magnitude of the influence on the coefficient of determination is 23.2%.